Determinants of the Association between Non‐Cardiac Chest Pain and Reflux. (November 2017) - Herregods, Thomas V K; Bredenoord, Albert J; Oors, Jacobus M; Bogte, Auke; Smout, André J P M
Abstract : Objectives: Gastroesophageal reflux is considered to be the most common gastrointestinal cause of non‐cardiac chest pain (NCCP). It remains unclear why some reflux episodes in the same patient cause chest pain while others do not. To understand more about the mechanisms by which reflux elicits chest pain, we aimed to identify factors which are important in triggering chest pain. Methods: In this multicenter study, 120 patients with NCCP were analyzed using 24‐h pH‐impedance monitoring. In the patients with a positive association between reflux and chest pain, the characteristics of the reflux episodes which were followed by a chest pain episode were compared with chest pain‐free reflux episodes. Results: Using 24‐h pH‐impedance monitoring, 40% of the NCCP patients were identified as having reflux as a possible cause of their chest pain. Reflux episodes that were associated with chest pain had a higher proximal extent ( P =0.007), a higher volume clearance time ( P =0.030), a higher 15‐minute acid burden ( P =0.041), were more often acidic ( P =0.011), had a lower nadir pH ( P =0.044), and had a longer acid duration time ( P =0.027) than reflux episodes which were not followed by chest pain. Patients who experienced typical reflux symptoms were more likely to have reflux as the cause of their chest pain (52 vs. 31.4%, P =0.023). Conclusions: The presence of a larger volume of acid refluxate for a longer period of time appears to be an important determinant of perceiving a reflux episode as chest pain. 24‐h pH‐impedance monitoring is an important tool in identifying gastroesophageal reflux as a potential cause of symptoms in patients with NCCP.